The effectiveness of suggested training program according to the Trends in International Mathematics and Science Study (TIMSS) in developing the teaching skills of intermediate school science teachers and their student academic achievement - Al-Sulaihem, Hanan Ali (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at building suggested training program according to the Trends in International Mathematics and Science Study (TIMSS) for science teachers in the intermediate school, and measuring its effectiveness in teaching skills for a sample of intermediate school science teachers. The sample consisting of (29) 2nd intermediate grade science teachers in Riyadh representing the first sample divided into (14) teachers in the experimental group who were trained on the suggested program and (15) in the control group who haven’t trained and investigating the effect of that on academic achievement for a sample consists of (300) 2nd intermediate grade science students divided into two groups: the first is experimental group consisting of (150) students taught (the substance and energy unit) by the teachers of the experimental group, the control group includes of (150) students taught the (substance and energy unit) by the teachers of the control group. To achieve this objective, a list of teaching skills required to intermediate school teachers according to the Trends in International Mathematics and Science Study (TIMSS), and preparing the test tools which are the teaching skills observation card according to the Trends in International Mathematics and Science Study (TIMSS). In the test of achievement in the unit of (Substance and Energy) from the science curriculum of 2nd intermediate grade in the first semester, and after the pretest and posttest for the study tools, the study revealed the following results: - There is statistical different at the level of (0.01) between the two averages of teachers’ degrees in the experimental and control group in the posttest for all teaching skills in the fields of (planning, implementation, and assessment) and the overall degree of teaching skills is for the benefit of the degrees of science teacher average in the experimental group in all cases. The Trends in International Mathematics and Science Study (TIMSS) have a very great effect in developing the teaching skills in the fields of (planning, implementation, and assessment) and the overall degree of teaching skills for the science teachers in the experimental group. - There is statistical different at the level of (0.01) between the averages of the experimental group students’ degrees taught by the experimental and control group teachers in the posttest for the all levels (Knowledge, Application, Deduction) and the overall degree average of the experimental group. The Trends in International Mathematics and Science Study (TIMSS) has a very great effect in developing the two levels of (Knowledge, Application) and the overall degree of academic achievement. the effect of the program is average in developing the level of (deduction).